Are there clinically relevant anatomical differences of the proximal femur in patients with mild dysplastic and primary hip osteoarthritis? A CT-based matched-pairs cohort study. Issue 11 (November 2019) - Innmann, M.M.; Hasberg, S.; Waldstein, W.; Grammatopoulos, G.; Gill, H.S.; Pegg, E.C.; Aldinger, P.R.; Merle, C.
Abstract : AIM: To investigate the three-dimensional anatomy and shape of the proximal femur, comparing patients with secondary osteoarthritis (OA) due to mild developmental dysplasia of the hip (DDH) and primary hip OA. MATERIALS AND METHODS: This retrospective radiographic computed tomography (CT)-based study investigated proximal femoral anatomy in a consecutive series of 84 patients with secondary hip OA due to mild DDH (Crowe type I&II/Hartofilakidis A) compared to 84 patients with primary hip OA, matched for gender, age at surgery, and body mass index. RESULTS: Men with DDH showed higher neck shaft angles (127±5° vs. 123±4°; p <0.001), whereas women with DDH had a larger femoral head diameter (46±4 vs. 44±3 mm; p =0.002), smaller femoral offset (36±5 vs. 40±4 mm; p <0.001), decreased leg torsion (25±13° vs. 31±16°; p =0.037), and a higher neck shaft angle (128±7° vs. 123±4°; p <0.001) compared to primary OA patients. Similar patterns of the three-dimensional endosteal canal shape of the proximal femur, but a high inter-individual variability for femoral canal torsion at the meta-diaphyseal level were found for DDH and primary OA patients. CONCLUSION: Standard cementless stem designs are suitable to treat patients with secondary hip OA due to mild DDH; however, high patient variability and subtle anatomical differences in the proximal femur should be respected. Highlights: Men with DDH showed higher neck shaft angles compared to primary hip OA. Women with DDH had a larger femoral head diameter, smaller femoral offset, decreased leg torsion and a higher neck shaft angle. Patients with DDH and primary OA showed similar patterns of the three-dimensional endosteal canal shape of the proximal femur. A high inter-individual variability for femoral canal torsion at the meta-diaphyseal level was observed in DDH patients. Hip arthroplasty can be performed with standard cementless stem designs in most of the patients with hip OA due to mild DDH.